Analysis of stress and stabilization in adolescent with osteoporotic idiopathic scoliosis: finite element method. Issue 1 (2nd January 2023) - Zhang, Qiaolin; Zhang, Yan; Chon, Teo. Ee; Baker, Julien S.; Gu, Yaodong
Abstract: Objective: To explore the effect of osteoporosis on the stress, stability, and lumbar intervertebral disc of AIS lumbar vertebrae by finite element method. Better understand the biomechanical characteristics of osteoporotic scoliosis. Methods: Based on the CT images of normal lumbar vertebrae and lumbar vertebrae with AIS, the finite element models were established to simulate the estimated osteoporosis by changing the Young's modulus of cortical bone, cancellous bone, and endplate. Four finite element models of normal lumbar, osteoporotic lumbar, normal AIS lumbar and osteoporotic AIS lumbar were established, and the same load and boundary conditions were applied respectively. The displacement, stress, and intervertebral disc strain of the four models were compared to explore the effect of osteoporosis on the stability and injury risk of AIS. Results: After suffering from osteoporosis, under the same load, the displacement of lumbar spine increases, the stability decreases, and the stability of AIS lumbar spine decrease more obviously, especially under extension load. Suffering from osteoporosis will increase the stress of lumbar spine, AIS lumbar spine increases more obviously, and the stress is more concentrated, Osteoporotic lumbar spine only affects the strain of intervertebral disc when AIS lumbar spine bends on the concave side, resulting in greater strain behind the concave side of intervertebral disc. Conclusions: AIS patients with OP have lower lumbar stability, a higher risk of fracture of lumbar vertebrae, and spinal nerves are more likely to be compressed by intervertebral discs. OP can aggravate the scoliosis of lumbar vertebrae.